Involvement of the Catecholamine in Glucagon-Induced Thermogenesis in Duckling (Carina Moschata) - M. Slimani (De Gruyter, 2007)
Physiological studies have shown that glucagon is a potential mediator of nonshiveringthermogenesis in birds. The present work was undertaken in order to investigatewhether the observed thermogenesis results from a direct action of glucagon onavian thermoregulatory mechanisms or in fact requires the participation of thecatecholamines.We focused our study on the effects of central glucagon on plasma catecholamine andheart rate on cold acclimated and glucagon treated ducklings in cold environment.Our results showed that cold exposure (4 °C) induced an increase of circulatingnorepinephrine in thermoneutrality (42 %) and cold acclimated (43 %) but notsignificantly in glucagon treated, while epinephrine decreased only in thermoneutrality(-45 %). After glucagon injection, circulating epinephrine increased in thermoneutrality(280 %) and CA (516 %), whereas norepinephrine concentrations decreased only inthermoneutral ducklings (-23 %). Plasma norepinephrine and epinephrine remainedunchanged in glucagon treated ducklings. Injection of glucagon caused a decrease inheart rate in thermoneutral duckling whereas it had no effect on cold acclimated andglucagon treated ducklings.The large increase in epinephrine levels in cold acclimated and thermoneutral ducklingsmay be due to a massive release of adrenal catecholamine in response to the conditions.Treatment with glucagon twice daily rendered probably ducks insensitive to the effectof intra-cerebroventricular glucagon injection